Proposed Business Strategy For Technical Service Department (Tsd) Pt Traktor (The Indonesian Journal of Business Administration, 2014)
Abstract - Technical Service Department (TSD Dept.) is one department under the auspices of the Product Support Division PT TRAKTOR that established in 1970 and become authorized dealer for â€œTANGGUHâ€ product in Indonesia in 1971. Main task of TSD is performing service and maintenance for â€œTANGGUHâ€ product, to support After Sales Service â€œTANGGUHâ€ product in Indonesia. Following the growth of heavy equipment maintenance business, TSDâ€™s revenue during the last few years also increased. However, when looking at the financial statements for two consecutive years (2011 & 2012) TSD still had operating losses while in that period the business in good condition and very conducive for TSD to make a profit. In order to improve TSDâ€™s productivity, efficiency, and implement new business model, new strategy is required by determining Directional Strategy, Business Strategy, and Functional Strategy. The strategy is formulated then followed up with its implementation plan through the work program for each function in the company within next 5 years. The successful of these strategies is depends on people, organization, and support system readiness.Â Keywords: Industrial Equipment Maintenance, Business Strategy, TOWS Matrix, Canvas Business Model.